Kajian pencemaran oleh enjin petrol; A simulation study on the diesel engine fuel injection system; A study on the prediction of combustion performance in a diesel engine; Performance of electric motors; Numerical modeling in a gasoline engine / [mikrofilem] - Mohd. Noor Azli Isa; Norizam Mohd. Ishak; Shamsul Daud; Vijayan R. Gopalakrishnan; Zulkiply A Rahman (Sekudai : UTM, 1994)
Project paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 1994